Successful pregnancy outcome in a case of idiopathic primary hypoparathyroidism with seizure disorder: a case report - Rajbhar, Sarita; Majumdar, Sagarika; Trigunait, Pragati; Thakur, Pushpawati; Shikha, Taru; Rastogi, Aparajita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Hypoparathyroidism, a disorder of low parathyroid hormones resulting in hypocalcemia and hyperphosphatemia, is relatively a rare occurrence in pregnancy. Nevertheless, it has been reported to cause significant maternal and neonatal morbidity and even mortality in severe cases. Dynamic changes in serum calcium during pregnancy superimposed with the inherent defect in the parathyroid gland and calcium metabolism in these patients make it even more difficult to monitor and manage the patient. We report a case of idiopathic primary hypoparathyroidism with seizure disorder, managed with aggressive monitoring and timely decision making, resulting in a favorable outcome.